A central arteriovenous fistula reduces systemic hypertension in a mouse model - Anand Brahmandam, MD; Rafael Alves, BM; Hao Liu, MD; Luis Gonzalez, PhD; Yukihiko Aoyagi, MD; Yuichi Ohashi, MD; John T. Langford, MD; Carly Thaxton, MD; Ryosuke Taniguchi, MD, PhD; Weichang Zhang, MD, PhD; Hualong Bai, MD, PhD; Bogdan Yatsula, PhD; et al. (JVS - Vascular Science)
Objective: A central arteriovenous fistula (AVF) has been proposed as a potential novel solution to treat patients with refractory hypertension. We hypothesized that venous remodeling after AVF creation in the hypertensive environment reduces systemic blood pressure but results in increased AVF wall thickness compared with remodeling in the normotensive environment. Methods: A central AVF was performed in C57BL6/J mice previously made hypertensive with angiotensin II (Ang II); mice were sacrificed on postoperative day 7 or 21. Results: In mice treated with Ang II alone, the mean systolic blood pressure increased from 90 ± 5 mmHg to 160 ± 5 mmHg at day 21; however, in mice treated with both Ang II and an AVF, the blood pressure decreased with creation of an AVF. There were significantly more PCNA-positive cells, SM22α/PCNA-positive cells, collagen I deposition, and increased Krüppel-like Factor 2 immunoreactivity in hypertensive mice with an AVF compared with normotensive mice with an AVF. Conclusions: These data show that a central AVF decreases systemic hypertension as well as induces local alterations in venous remodeling.